The Density of Recombination-Associated Genomic Features Does Not Generally Explain the Broad-Scale Crossover Patterns in Chicken and Guinea Fowl - Luis F. Rossi; María Inés Pigozzi (Animals)
Meiotic recombination is essential for chromosomal segregation and facilitates the exchange between homologs, which leads to the transmission of new combinations of linked alleles to the progeny. The eukaryotic meiotic machinery is generally highly conserved, but the frequency of crossover occurrence can vary dramatically across species and populations, between individuals, and across sexes. The chicken and the guinea fowl exhibit interspecific variation in the distribution of crossovers along their largest chromosomes. In many organisms, an association has been observed between the preferred crossover location and certain sequence parameters, such as high GC content, CpG islands, or gene promoters. Here, we compared the distribution of these genomic parameters with the recombination landscape, represented by MLH1 focus frequencies, in the two birds. We found an association between GC content density and recombination in the chicken, but the remaining parameters showed weak or no association with recombination, especially in the guinea fowl. We conclude that despite the different broad-scale crossover distribution, the investigated genomic parameters remained remarkably similar in these two species. We suggest that the density of these genomic features is more likely related to microscale variations in recombination rates, such as those determined by open chromatin configurations.